Correlation of Discordance between Remnant Lipoprotein Cholesterol and Non-high-density Lipoprotein Cholesterol and Severity of Coronary Stenosis - CHEN Yan, LYU Zhibo, ZHAO Xin (Zhongguo quanke yixue, 2023)
Background Discordance between blood lipids has been shown to be associated with the occurrence of serious coronary events in patients with coronary artery disease (CAD) , which may lead to the overestimation or underestimation of the risk of coronary events. The clinical significance of discordance between residual lipoprotein cholesterol (RLP-C) and non-high-density-lipoprotein cholesterol (non-HDL-C) still remains unclear in present. Objective To determine the correlation of discordance between RLP-C and non-HDL-C and the severity of coronary artery stenosis in patients with CAD. Methods A total of 398 patients with coronary artery disease receiving coronary angiography from January 2004 to December 2014 with complete coronary angiographic records and Gensini score which can be fully calculated from a previous normal high blood pressure cohort study database were retrospectively analyzed and divided into 4 groups based on the median RLP-C and non-HDL-C levels in the cohort, including concordantly low RLP-C group (RLP-C<medianRLP-C and non-HDL-C<mediannon-HDL-C, n=129) , discordantly low RLP-C group (RLP-C<medianRLP-C and non-HDL-C≥mediannon-HDL-C, n=69) , discordantly high RLP-C group (RLP-C≥medianRLP-C and non-HDL-C< mediannon-HDL-C, n=67) , concordantly high RLP-C group (RLP-C≥medianRLP-C and non-HDL-C≥mediannon-HDL-C, n=133) . The severity of coronary stenosis was evaluated by using the Gensini scoring system. The baseline data was compared among the 4 groups and the correlation between RLP-C and non-HDL-C was analyzed by Pearson's linear correlation. The correlation of discordance between RLP-C and non-HDL-C and severity of coronary stenosis was explored by Logistic regression analysis. Results Discordance were observed in 34% (136/398) of the included patients. Severe coronary stenosis was observed in 15.5%, 18.9%, 32.3%, and 24.9% of patients in the concordantly low RLP-C group, discordantly low RLP-C group, discordantly high RLP-C group and concordantly high RLP-C group. Logistic regression analysis results showed that there was no significant correlation of discordance between RLP-C and non-HDL-C and severity of coronary artery stenosis (P<0.05) . Logistic regression analysis results of the patients in discordantly low RLP-C group and discordantly high RLP-C group showed that after adjusting for confounders such as sex, age, smoking, alcohol consumption, statin application and presence of diabetes, the low RLP-C level was not associated with the development of severe coronary stenosis 〔OR=0.958, 95%CI (0.473, 1.939) , P=0.905〕, high RLP-C was associated with the development of severe coronary artery disease 〔OR=2.084, 95%CI (1.110, 3.912) , P=0.022〕 in patients in the discordantly groups. In addition, RLP-C remained a strong predictor of the risk of severe coronary artery disease〔OR=1.911, 95%CI (1.253, 2.914) , P=0.003〕after multivariate Logistic regression model adjustment. Conclusion The discordance between RLP-C and non-HDL-C is correlated with severity of coronary stenosis in patients with high RLP-C and low non-HDL-C levels, which has the potential to be a novel risk factor for predicting severe coronary stenosis in CAD patients on the basis of traditional lipid indicators, independent of age, sex and other risk factors.